DIGITAL TECHNOLOGIES IN AESTHETIC DENTISTRY: TOOL FOR PLANNING AND EXECUTING RESTORATIVE TREATMENTS : tecnologias digitais em odontologia estética: ferramentas para o planejamento e execução de tratamentos restauradores - Rodrigo Lins (Revista de Ciências da Saúde Nova Esperança, 2025)
Digital technologies have played an essential role in contemporary dentistry, especially in the scheduling and execution of aesthetic treatments. This study aims to evaluate the available technologies and their applications, advantages, disadvantages, and future perspectives. Integrative literature review on the use of digital tools with a focus on restorative procedures, conducted through research in the PubMed, Lilacs, and Cochrane databases in May 2024, in English and Portuguese. Of the 193 articles found in the search, 46 studies in English and Russian were included in this review after analysis according to the parameters: text available to read in full, approach to digital tools, focus on dental aesthetics and relation to the dentistry specialty. And exclusion parameters: articles restricted to the areas of prosthodontics, endodontics, implantology, orthodontics and oral and maxillofacial surgery. In these studies, several categories of technologies were identified for various purposes in aesthetic planning and treatment, such as: software, scanners, tomographs, 3D printers, chairside systems, as well as artificial intelligence (AI) and augmented reality (AR). All these alternatives promise to expand the possibilities of digital scheduling, promoting greater precision and personalization in therapeutic resources. The digital workflow offers reduced clinical time, predictability, and precision in planning and treatment but does not eliminate the need for clinical judgment, experience, and mastery of the tools. The integration of these tools aims to optimize clinical workflow, improve communication with the patient and enhance aesthetic and functional results, consolidating digitalization as a pillar of the future of dentistry.